Functions of Prdm16 in thermogenic fat cells - Ishibashi, Jeff (Temperature (Austin), 2015)
The PR-domain containing 16 (Prdm16) protein is a powerful inducer of the thermogenic phenotype in fat cells. In both developmental (brown) and induced (beige) thermogenic adipose tissue, Prdm16 has a critical role in maintaining proper tissue structure and function. It has roles throughout the course of differentiation, beginning with lineage determination activity in precursor cells, and continuing with coactivator functions that enable and maintain thermogenic gene expression. These abilities are primarily mediated by interactions with other adipogenic factors, suggesting that Prdm16 acts to coordinate the overall brown adipose phenotype. Mouse models have confirmed that thermogenic adipose depends upon Prdm16, and that this type of fat tissue provides substantial metabolic protection against the harmful effects of a high fat/high energy diet. Activation of Prdm16, therefore, holds promise for stimulating thermogenesis in fat cells to reduce human obesity and its complications.